Cytokeratin 19 as a biomarker of highly invasive oral squamous cell carcinoma with metastatic potential. Issue 1 (January 2020) - Tanaka, Shoichi; Kawano, Shintaro; Hattori, Taichi; Matsubara, Ryota; Sakamoto, Taiki; Hashiguchi, Yuma; Kaneko, Naoki; Mikami, Yurie; Morioka, Masahiko; Maruse, Yasuyuki; Kitamura, Ryoji; Hamada, Eiki; et al.
Abstract: Objective: Cytokeratin (CK) 19 is a member of the acidic type I CK family. Recently, CK19 expression has been found in various tumor tissues; however, the significance of this remains unknown. The purpose of this study is to clarify the roles of CK19 in the progression of oral squamous cell carcinoma (OSCC). Methods: A total of 100 patients who had been diagnosed with OSCC at our department between January 2011 and December 2016 was included. The patients were divided into three groups based on an optimal cut-off points (5% and 77%) of the labeling index (LI) as follows: group A; LI < 5%, group B; 5%≤ LI < 77%, group C; LI ≥ 77%. Then, clinicopathological features and survival rates were compared among the groups. Results: Histologically high-grade tumors were significantly more common in group C than in groups A and B. Furthermore, the incidence of nodal metastasis was significantly higher in group C than in other groups. Intense CK19 immunoreactivity was detected in metastatic lymph nodes of groups B and C, but not from group A. Moreover, patients with advanced pN stage and extranodal extension were more common in groups B and C than group A. Disease-specific survival curves revealed poorer prognoses in group C. Conclusions: These results suggest that CK19 is involved in OSCC invasion and metastasis and could be a novel biomarker of highly invasive OSCC with metastatic potential.